The Coronal Structure of the Sun-Like Exoplanet-Host GJ 3021. Issue Volume 10:Issue S305(2014) (24th July 2015) - Alvarado-Gómez, J. D.; Cohen, O.; Hussain, G. A. J.; Grunhut, J.; Garraffo, C.; Drake, J.
Abstract: We present the results of a numerical simulation of the corona and wind structure of the Sun-like exoplanet-host GJ 3021 using a global magnetohydrodynamic (MHD) model. The simulation is driven by the radial component of the surface magnetic field recovered with the Zeeman Doppler Imaging (ZDI) technique. We consider two different ZDI input maps, which have similar large-scale structures but different spatial resolutions and field strengths. These maps arise from different but comparable models used to fit the observed circularly polarised spectra of the star. Our simulations show that the structure of the inner corona is consistent among the considered cases. Larger discrepancies are found in the wind structure, in particular in the radial wind speed and the Alfvén surface topology. These elements can have a significant impact on the mass loss and angular momentum loss predicted for this system and in other studies based on this numerical data-driven approach.